Intercultura e educação - Reinaldo Fleuri Matias (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
Interculture refers to a complex field of debates around plural conceptions and proposals concerning the relationship between differing sociocultural identity processes. It particularly focuses on the possibility of respecting the differences and integrating them into a unity that does not dissolve them. Interculture has emerged both as a new epistemological perspective and an interdisciplinary and transversal object of study. It discusses and theorises about complexity (beyond issues of plurality or diversity), as well as ambivalence or hybridisation (beyond reciprocity or the linear evolution of ideas), with reference to the processes of creating meaning within intergroup and intersubjective relationships, which build identity fields in terms of ethnicity, generation, gender and social action. Building on different theoretical-methodological paths and concepts, this theme has been challenging the field of Education in Brazil, which has replied in the form of studies and proposals concerning issues such as Indian education, affirmative action towards ethnic minorities, processes of social inclusion of individuals with disabilities, gender movements, valuing of child cultures and movements concerned with the third age. The most recent research studies presented at 25th Annual Meeting of ANPEd seem to unfold new understandings for the analysis of cultural differences and identities in the field of educational practices. Moving beyond a fixed, hierarchised, discipline- bound and normalised view of cultural diversity, a hybrid, fluid and polysemic and, at the same time, tragic and promising area concerning difference emerges. It is built within the chinks and glances of the enunciations of different subjects and sociocultural identities. It views education as a process built upon tense and intense relationships between subjects, generating interactive contexts that dynamically interrelate with the plural cultural contexts in which different individuals develop their identities, thus making them creative and formative environments par excellence